The Persian Empire and Classical Political Thought: A Panoramic View - Treuk Medeiros de Araujo, Matheus (Revista Archai, 2018)
AchaemenidPersia had a deep and enduring impact in classical Greek political thought. After the submission of the Ionian Greeks and the Persian Wars, the idea of a territorial empire, originally a foreign reality, became increasingly important among Greek historiographers and would be of paramount importance to the rise of Hellenicity. During the Late Classical and Hellenistic Period, the opposition between “free” Greeks and “slavish” Persians on the ground of constitutional differences became so strong that it pervasively permeated the works of Aristotle and the political propaganda of Alexander. Evaluation of individual Persian monarch’s virtues (and vices) was central in Greek examples of political leadership and raises many interesting questions to modern scholars. A panoramic view of some of the main subjects in Greek political works is therefore needed to highlight the importance of Persia as a stimulus and concern of classical thought.